Analyze of Dramaturgy to Self Concept of Pupil TMI Al-Amien Prenduan (Erving Gofman’s Theory Analysis) - Nisak, Khoirun; Salimah, Ifa Dotus; Ma’ruf, Amar; Syaifuddin, Syaifuddin (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
Human social life always be related with society interacting anywhere, anytime, and their lives present their selves as a theatre performers whose appearance can change at any time depending on the context. It happens in human life, whoever we are, and in any condition, we always interact in symbols. Maybe without us realizing it, it all happens in every "scene", in a "play" of life. This research uses descriptive analysis, using an interpretive paradigm. By starting from the phenomenon being studied to produce a theory, the goal is used to understand the meaning of the experience of a person, group. But education that can be drawn from the vile events that a person has gone through. By analyzing from sources that are directly on the object and relevance to research. Reviewing the self-presentations displayed by the students by looking at the backstage and front stage. The results of this analysis, the students of TMI Al-Amien Prenduan in their daily lives can manage the two allocations of the place, they know their position how they must display their character setting in front of the supervisors of the cottage, and position their original character when behind the supervisor of the cottage when they are free from supervision.